The Authority of Notaries in the Preparation of Deeds Concerning Credit Guarantees as a Form of Resolution for Non-Performing Loans - Aptaningsih, Ni Made Indah; Senastri, Ni Made Jaya; Jaya Utama, I Wayan Kartika (Journal of Law, Politic and Humanities, 2025)
Non-performing loans pose a serious challenge in the banking sector, especially for Rural Credit Banks (BPR). One of the solutions is through the takeover of collateral or AYDA. This study aims to examine the authority of notaries in the creation of deeds concerning credit guarantees as part of the non-performing loan resolution process. The research method used is empirical with a qualitative approach, through interviews with three notaries/PPAT in the Denpasar area and one notary/PPAT in the Badung area. The data collection techniques used are Purposive Sampling, Interview Technique, Observation Technique, and Documentation Technique. The research results show that notaries are authorized to draft the AYDA deed based on non-performing loan collateral still burdened by a mortgage, based on an agreement between the creditor and the debtor. The debtor must first create a statement letter of collateral surrender to the creditor, which is subsequently followed up by the Notary with the drafting of several deeds for the benefit of both parties, namely the power of attorney, debt settlement agreement deed, sale and purchase deed, sale and purchase binding agreement, and eviction agreement.